Biomedical Engineering Research Based on Computer Propagation Technology: Treatment of neurodigestive diseases - Li, Linyan; Chen, Hao; Shi, Enquan; Wang, Han; Wang, Jingyue; Lin, Yixian; Yu, Tao; Huang, Yaxi; Dan, Han; Wang, Chenchen; Yi, Qin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
With the support of the Institute of Cancer Hospital of Chifeng University, Sarkov and Markov Memorial Health Informatics Laboratory designed a new working concept of innovative Nursing by using neural network and Brain–computer interface technology. The research team proposed a direct connection between human or animal brain (or brain cell culture) and external equipment. In the case of one-way Brain–computer interface, the computer may accept commands from the brain. Using this point to detect the emotion of patients after surgery and carry out necessary gourds, a two-way information exchange method and model of two-way Brain–computer interface are also proposed. The potential non-invasive Brain–computer interface designed by us has been deeply studied, mainly because of its good time resolution, ease of use, portability and relatively low price. Especially in the specific application and working practice of EEG (Electroencephalography), our achievements directly meet the application of clinical institutions.